Metastatic malignant melanoma of the urinary bladder: A case report and review of the literature - Cumhur Selçuk Topal; Gözde Kır; Taner Daş; Billur Sarbay; Muzaffer İlkay Tosun (Wolters Kluwer Medknow Publications, 2016)
Metastatic bladder tumors constitute <5% of all bladder tumors and metastatic malignant melanoma of the urinary bladder is very rare. We present a case report of a metastatic malignant melanoma of the urinary bladder. A 70-year-old woman without any apparent significant clinical history was admitted to the Department of Urology for gross hematuria. Microscopic findings of the transurethral resection specimen revealed fascicles, sheets, and diffuse areas composed of oval and fusiform cells with focal pigmentation. Immunohistochemical analysis revealed that the tumor cells were positive for human melanoma black-45, Melan-A, and S100, and negative for pancytokeratin. Subsequently, we contacted the patient and learned that she was admitted to the Department of Ophthalmology for painless and progressive visual field loss 15 years ago. She had been diagnosed with a primary ocular (uveal) melanoma. A detailed patient history coupled with histological and immunohistochemical findings were necessary to make the final diagnosis of metastatic melanoma.